2012
DOI: 10.1002/cam4.19
|View full text |Cite
|
Sign up to set email alerts
|

Id1 and Id3 expression is associated with increasing grade of prostate cancer: Id3 preferentially regulates CDKN1B

Abstract: As transcriptional regulators of basic helix–oop–helix (bHLH) transcription and non-bHLH factors, the inhibitor of differentiation (Id1, Id2, Id3, and Id4) proteins play a critical role in coordinated regulation of cell growth, differentiation, tumorigenesis, and angiogenesis. Id1 regulates prostate cancer (PCa) cell proliferation, apoptosis, and androgen independence, but its clinical significance in PCa remains controversial. Moreover, there is lack of evidence on the expression of Id2 and Id3 in PCa progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…We identified a strong candidate for this role, inhibitor of differentiation 1 ( ID1 ), which was upregulated in LNCaP APIPC compared with LNCaP shAR/pATK (∼10-fold by RNA-seq; q < 0.001; 5-fold byqRT-PCR) (Figure 7A). ID1 expression is induced by exogenous FGF and bone morphogenetic protein via MAPK pathway activation (Langenfeld and Langenfeld, 2004; Passiatore et al, 2011), prevents differentiation by binding cell lineage-specific transcription factors (Perk et al, 2005), and has been associated with poorly differentiated PC (Coppe et al, 2004; Sharma et al, 2012). Notably, other ID family members were also increased in LNCaP APIPC and the LuCaP173.2 DNPC PDX (Figure 7B).…”
Section: Resultsmentioning
confidence: 99%
“…We identified a strong candidate for this role, inhibitor of differentiation 1 ( ID1 ), which was upregulated in LNCaP APIPC compared with LNCaP shAR/pATK (∼10-fold by RNA-seq; q < 0.001; 5-fold byqRT-PCR) (Figure 7A). ID1 expression is induced by exogenous FGF and bone morphogenetic protein via MAPK pathway activation (Langenfeld and Langenfeld, 2004; Passiatore et al, 2011), prevents differentiation by binding cell lineage-specific transcription factors (Perk et al, 2005), and has been associated with poorly differentiated PC (Coppe et al, 2004; Sharma et al, 2012). Notably, other ID family members were also increased in LNCaP APIPC and the LuCaP173.2 DNPC PDX (Figure 7B).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have shown that increased ID1 expression in PCa [12] is associated with castration resistance and resistance to chemotherapeutic agents [4345]. Since ID4 lacks a DNA binding domain hence most of its regulatory actions may involve interactions with other proteins.…”
Section: Discussionmentioning
confidence: 99%
“…After incubation with primary and secondary antibodies, the membranes were developed using an ECL kit (GE Life Sciences, Piscataway, NJ) as described earlier 51 . The ID-1, -2, -3, -4 and E47 antibodies used in this study have been validated as described in our previous studies 5153 .…”
Section: Methodsmentioning
confidence: 99%